Review Artikel: Penggunaan Polimer dalam Formulasi Gel Minyak Atsiri - Nurlia Julianti; Aliya Azkia Zahra (Poltekkes Kemenkes Padang, 2024)
Essential oil gel is a preparation that contains essential oil in gel form. Gelling agent is an important factor that affects the physical properties produced such as colour, shape, odour, spreadability, adhesion and viscosity. The purpose of this review article is to look at the use of various types of polymers as gelling agents in the formulation of essential oil gels and how it can affect the physical properties. The method of writing this article is to use the literature review method, which is research using data collection from literature sources such as articles that are relevant to the topic. The data sources used in this article are 50 articles using national and international journals published in the last 10 years, namely 2014 - 2024. The results obtained show that the physical properties of essential oil gels produced can be influenced by the active substance and the type of polymer used, synthetic polymers with the type of gelling agent carbomer is the most widely used gelling agent based on the amount and carbomer gelling agent can produce good physical properties in essential oil gels. Thus, the conclusion of this review article is that the choice of polymer type as a gelling agent in the formulation of essential oil gel can affect the physical properties produced in essential oil gel. It is suggested that further research can consider well in the development of essential oil gel formulations.